Aligned but Unequal: The Uneasy Relationships Between Queer Studies and Cultural Studies in Indonesia - Ferdiansyah Thajib (Retorik: Jurnal Ilmu Humaniora)
Queer Studies and Cultural Studies are closely intertwined, each offering valuable perspectives on the relationship between power, identity, and social norms. Both fields emerged as responses to marginalization, challenging dominant social and political norms. However, unlike Cultural Studies in Indonesia, Queer Studies has yet to establish a strong academic presence. The primary obstacle is the political and social climate, which restricts space for queer discourse in both public and academic arenas. Despite this, queer knowledge continues to evolve in Indonesia, often woven into gender studies, literature, and cultural studies, and more prominently, outside of academia. These conditions, combined with the absence of a formal curriculum, make it challenging to develop Queer Studies cohesively in Indonesia. This paper adopts a scoping review approach, interwoven with personal reflections drawn from my experiences as a researcher situated across two academic realities—Indonesia and abroad—as well as from a decade of engagement with fellow queer scholars in both contexts. It opens by mapping by tracing the development of Queer Studies at transnational, regional, and national levels. The discussion then focuses on the dynamic interplay between Queer Studies and Cultural Studies in Indonesia. Through this inquiry, it becomes evident that the relationship between the two not only reflects a mutually enriching intellectual exchange but also reveals tensions that mirror power dynamics in the production of knowledge. These tensions take hold not only at the discursive level, but also in material, institutional, and affective forms.